The Home-Market Effect and Bilateral Trade Patterns - Hanson, Gordon H; Xiang, Chong (American Economic Review, 2004)
We test for home-market effects using a difference-in-difference gravity specification. The home-market effect is the tendency for large countries to be net exporters of goods with high transport costs and strong scale economies. It is predicted by models of trade based on increasing returns to scale but not by models of trade based on comparative advantage. In our estimation approach, we select pairs of exporting countries that belong to a common preferential trade area and examine their exports of goods with high transport costs and strong scale economies relative to their exports of goods with low transport costs and weak scale economies. We find that home-market effects exist and that the nature of these effects depends on industry transport costs. For industries with very high transport costs, it is national market size that determines national exports. For industries with moderately high transport costs, it is neighborhood market size that matters. In this case, national market size plus market size in nearby countries determine national exports.